2009
DOI: 10.1007/s10822-009-9295-y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of peptides containing D-amino acids: implications on cyclization

Abstract: Cyclic peptides are therapeutically attractive due to their high bioavailability, potential selectivity, and scaffold novelty. Furthermore, the presence of D-residues induces conformational preferences not followed by peptides consisting of naturally abundant L-residues. Therefore, comprehending how amino acids induce turns in peptides, subsequently facilitating cyclization, is significant in peptide design. Here, we performed 20-ns explicit-solvent molecular dynamics simulations for three diastereomeric pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 41 publications
4
20
0
Order By: Relevance
“…Molecular dynamics simulations and quantum mechanics calculations were also applied to these three peptide thioesters. 18 The results are consistent with the cyclization tendencies.…”
Section: Resultssupporting
confidence: 80%
“…Molecular dynamics simulations and quantum mechanics calculations were also applied to these three peptide thioesters. 18 The results are consistent with the cyclization tendencies.…”
Section: Resultssupporting
confidence: 80%
“…This work has demonstrated that 3 compounds containing these motifs were significantly more potent than the natural product peptide, San A-amide 6. Our work has been validated by several current examples in the recent literature where cyclic peptides, and specifically pentapeptides, with both an N-methyl and D-amino acid lock the macrocycle into a single conformation 1416. Data from these studies suggest that the compounds, once locked into a major conformation, will be appropriately positioned as a beta or gamma turn, which is likely to lead to a well-defined, high affinity interaction with the protein target 17, 18…”
Section: Introductionsupporting
confidence: 64%
“…Peptides consisting only of l-residues, devoid of other turn-inducing structures, will often not cyclize until the C-terminal α-carbon has epimerized to the d-configuration 35 . The effect of d-amino acids on peptide macrocyclization have also been modelled theoretically 36 .…”
Section: Conformational Elements That Help Bring the Ends Togethermentioning
confidence: 99%